2019
DOI: 10.1016/j.jclinepi.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Justification and reporting of subgroup analyses were lacking or inadequate in randomized controlled trials

Abstract: Objectives: The aim of the article was to assess the appropriateness and rationales of subgroup analyses planned in protocols of randomized controlled trials and reported in subsequent corresponding trial publications. Study Design and Setting: We searched PubMed to identify trial protocols published in journals during 2006e2017. From a total of 3,774 initially identified records, we included a random sample of 479 protocols and identified 280 trial publications corresponding to the included protocols. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Thus, our findings in the addiction clinical trial literature fitted within the broader context . In addition to our previous studies, several others suggest that selective reporting of outcomes and analyses is common in clinical trials. Beyond selective outcome reporting, our study shows that a significant proportion of RCTs in our sample were registered after patient enrollment ended or were not registered at all.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our findings in the addiction clinical trial literature fitted within the broader context . In addition to our previous studies, several others suggest that selective reporting of outcomes and analyses is common in clinical trials. Beyond selective outcome reporting, our study shows that a significant proportion of RCTs in our sample were registered after patient enrollment ended or were not registered at all.…”
Section: Discussionsupporting
confidence: 77%
“…while the design effect for testing treatment effect heterogeneity with respect to an individual-level covariate is implied from Equations (11) and (15),…”
Section: Basic Setting With One Covariatementioning
confidence: 99%
“…Then given the value of n, we simulate individual-level outcomes Y ij from model (3), where we choose 2 = 0.25 and 3 = 0.1. As we have explained in Section 3.1, these regression parameters are ancillary to sample size determination as they are not part of Equation (11). A total of 5000 data replicates are generated for each scenario, and the linear mixed effects model (3) is fit to each data set using the restricted maximum likelihood estimation (REML).…”
Section: Simulation Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subgroup analyses are subject to multiple methodological challenges which can complicate their interpretation, including increased risks of type I error due to multiple testing and low statistical power [20]. Some reviews have found that subgroup analyses are often poorly justified, infrequently pre-specified, and inadequately reported [21]. While such challenges may seem to discourage their use, lack of disaggregation or descriptive detail means that judgments about the policy relevance of the evidence to people who live with social disadvantage may be difficult for decision-makers who are using the evidence to inform and implement policies, programs, or individual patient care.…”
Section: Introductionmentioning
confidence: 99%